Bone quality associated with daily intake of coffee: a biochemical, radiographic and histometric study - Lacerda,Suzie Aparecida (2010)
Caffeine induces loss of calcium and influences the normal development of bone. This study investigated the effects of coffee on bone metabolism in rats by biochemical measurement of calcium, bone densitometry and histometry. Male rats, born of female treated daily with coffee and with coffee intake since born, were anesthetized, subjected to extraction of the upper right incisor, and sacrificed 7, 21 and 42 days after surgery. Blood and urine samples were taken, and their maxilla radiographed and processed to obtain 5-µm-thick semi-serial sections stained with hematoxylin and eosin. The volume and bone quality were estimated using an image-analysis software. The results showed significantly greater amount of calcium in the plasma (9.40 ± 1.73 versus 9.80 ± 2.05 mg%) and urine (1.00 ± 0.50 versus 1.25 ± 0.70 mg/24 h) and significantly less amount in bone (90.0 ± 1.94 versus 86.0 ± 2.12 mg/mg bone), reduced bone mineral density (1.05 ± 0.11 versus 0.65 ± 0.15 mmAL), and lower amount of bone (76.19 ± 1.6 versus 53.41 ± 2.1 %) (ANOVA; p≤0.01) in animals treated with coffee sacrificed after 42 days. It may be concluded that coffee/caffeine intake caused serious adverse effects on calcium metabolism in rats, including increased levels of calcium in the urine and plasma, decreased bone mineral density and lower volume of bone, thus delaying the bone repair process.